PENGUATAN ADMINISTRASI LOGISTIK TNI AD DALAM RANGKA ASTA CITA MENUJU INDONESIA EMAS 2045 - Murtopo, Adi; Supriyono, Tjatur (PPM Sdirjianbang Akademi Militer, 2025)
The logistics administration of the Indonesian Army (TNI AD) is a strategic pillar that supports combat readiness, the effectiveness of military operations, and the sustainability of national defense development. In the context of achieving Asta Cita toward Golden Indonesia 2045, strengthening logistics administration is an urgent necessity. This study aims to analyze the current conditions, challenges, and strategies for strengthening TNI AD logistics administration using a literature review method. Data were collected from primary sources, such as official TNI AD documents, laws, and national policies, as well as secondary sources, including books, national and international journals, and research reports. Data analysis employed Miles and Huberman’s interactive model through data reduction, data display, and conclusion drawing, with validation conducted via source triangulation. The findings indicate that TNI AD logistics administration faces challenges related to technology, organizational structure, human resource competence, and strategic environmental dynamics. Strengthening strategies include digitalizing logistics systems, enhancing transparency and accountability, developing technology-adaptive human resources, and integrating logistics across military branches and government institutions. The relevance of logistics strengthening to Asta Cita lies in the development of superior human resources, infrastructure modernization, and governance reform. By adopting best practices from NATO, the United States, and Singapore, TNI AD can accelerate logistics modernization and contribute to realizing Golden Indonesia 2045.